2022
DOI: 10.1029/2021ef002433
|View full text |Cite
|
Sign up to set email alerts
|

A Bioeconomic Projection of Climate‐Induced Wildfire Risk in the Forest Sector

Abstract: Under the influence of climate change, wildfire regimes are expected to intensify and expand to new areas, increasing threats to natural and socioeconomic assets. We explore the environmental and economic implications for the forest sector of climate‐induced changes in wildfire regimes. To retain genericity while considering local determinants, we focus on the regional level and take Mediterranean France as an example. Coupling a bioeconomic forest sector model and a model of wildfire activity, we perform spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 86 publications
1
1
0
Order By: Relevance
“…Other factors, such as the location, land cover, urban cover and topography controlled to some extent fire regimes across space. Future changes projected in the European pyrogeography agreed with other studies indicating that most of the future increases are expected in the most fire-affected areas today (Carnicer et al, 2022;Jones et al, 2022;Pimont et al, 2022;Riviere et al, 2022). Additionally, our findings indicated that regions with a great extent of fuel available to burn in the transition zones (40-45°N) were more likely to shift toward a more fire prone regime in a warmer and drier climate.…”
Section: Historical and Future European Pyrogeographysupporting
confidence: 88%
See 1 more Smart Citation
“…Other factors, such as the location, land cover, urban cover and topography controlled to some extent fire regimes across space. Future changes projected in the European pyrogeography agreed with other studies indicating that most of the future increases are expected in the most fire-affected areas today (Carnicer et al, 2022;Jones et al, 2022;Pimont et al, 2022;Riviere et al, 2022). Additionally, our findings indicated that regions with a great extent of fuel available to burn in the transition zones (40-45°N) were more likely to shift toward a more fire prone regime in a warmer and drier climate.…”
Section: Historical and Future European Pyrogeographysupporting
confidence: 88%
“…Statistical models linking climate and environmental conditions to fires have received much attention under the global warming context (Abatzoglou et al, 2021;Barbero et al, 2014;Pimont et al, 2021;Riviere et al, 2022;Turco et al, 2018Turco et al, , 2019. We sought here to develop individual statistical models for each fire-regime component to simulate historical and future fire activity in Europe.…”
Section: Modeling Fire-regime Componentsmentioning
confidence: 99%
“…It provides a systemic description of the forest sector, considers interactions between ecological and economic dynamics, and is well-suited to exploring alternative futures and performing policy analyses (Latta et al 2013, Riviere and Caurla 2020). It has previously been used to address bioenergy production (Caurla et al 2018), climate change impacts (Riviere et al 2022) and pest outbreaks (Petucco et al 2020), albeit without considering salvage.…”
Section: The French Forest Sector Model (Ffsm)mentioning
confidence: 99%
“…While these models are often used to evaluate climate mitigation policies and project carbon budgets (Honkomp and Schier 2023), risks and uncertainties, including disturbances, have received limited attention (Chudy et al 2016). This is attributable to the models' deterministic nature, simplified representation of forest inventories, and focus on timber markets (Riviere et al 2022). Storms, in particular, have only been the focus of retrospective assessments (Caurla et al 2015, Henderson et al 2022.…”
Section: Introductionmentioning
confidence: 99%